An Alternative Method for Evaluation of Resistance to Low ph and Bile Salts in Probiotic Characterization of Lactobacillus Reuteri Strains. A Technical Note - Bolado-Martínez, Enrique; Pérez-Morales, Rosalva; Acedo-Félix, Evelia (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>A considerable amount of attention has been focused on the use of lactobacilli as probiotics. The use of microorganisms as probiotics must meet certain criteria, among these; the resistance to low pH and bile salts is of great importance. Different procedures have been designed to evaluate tolerance to gastrointestinal transit. Since resistance to low pH and bile salts is critical in the evaluation of probiotic strains, the aim of this study was to compare resistance to bile salts for 20 strains of porcine Lactobacillus reuteri that had been isolated from healthy pigs, using two different procedures based on exposure to low pH. Statistical analysis revealed no difference in resistance of the strains to bile salts whether pH was low or not. The use of low pH prior to exposure to bile salts therefore more closely represents physiological conditions that should be used for the evaluation of potential porcine probiotic lactobacilli. Further studies using digestive enzymes are required to evaluate resistance to gastrointestinal transit, since it is an important factor in the evaluation of strains with potential probiotic activity